2007
DOI: 10.1007/s00428-007-0434-3
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected diagnosis of cystic fibrosis at liver biopsy: a report of four pediatric cases

Abstract: We report here four cases of pediatric patients in whom the diagnosis of cystic fibrosis was made only after the histological examination of a liver specimen obtained by biopsy (three cases) or at autopsy (one case). There were two boys and two girls, aged 13 months to 7.5 years. None had a personal or familial history suggestive of cystic fibrosis. One patient, presenting with myocardial lesion and hepatomegaly, died of heart failure; at autopsy, the liver showed a typical aspect of focal biliary cirrhosis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…A very recent study in human failing heart found that the expression of the mature CFTR protein decreased significantly to 52% of CFTR levels in non-failing controls (141). Interestingly, it was reported recently that a pediatric patient who died of heart failure with significant myocardial lesion was retrospectively diagnosed as cystic fibrosis only after the histological examination of a liver biopsy (32). The exact functional and clinical significance of the changes in CFTR expression during hypertrophy and heart failure is currently not clear and merits further study.…”
Section: Phenotypic Study Of Cardiac Channelsmentioning
confidence: 99%
“…A very recent study in human failing heart found that the expression of the mature CFTR protein decreased significantly to 52% of CFTR levels in non-failing controls (141). Interestingly, it was reported recently that a pediatric patient who died of heart failure with significant myocardial lesion was retrospectively diagnosed as cystic fibrosis only after the histological examination of a liver biopsy (32). The exact functional and clinical significance of the changes in CFTR expression during hypertrophy and heart failure is currently not clear and merits further study.…”
Section: Phenotypic Study Of Cardiac Channelsmentioning
confidence: 99%
“…On the other hand, cases have been reported of paediatric patients in whom liver disease was the only manifestation of cystic fibrosis, and the diagnosis was made only following histological examination of a liver specimen obtained by biopsy or at autopsy [38 ]. Liver biopsy may provide important information on the type of the predominant lesion (steatosis or focal biliary cirrhosis), extent of portal fibrosis, rate of progression of liver disease and response to treatment.…”
Section: Diagnosismentioning
confidence: 99%
“…A very recent study in human failing heart found that the expression of the mature CFTR protein decreased significantly to 52% of CFTR levels in non‐failing controls (Solbach et al 2008). Interestingly, it was reported recently that a paediatric patient who died of heart failure with significant myocardial lesion was retrospectively diagnosed as cystic fibrosis only after the histological examination of a liver biopsy (Collardeau‐Frachon et al 2007). The exact functional and clinical significance of the changes in CFTR expression during hypertrophy and heart failure is currently not clear and merits further study.…”
mentioning
confidence: 99%